Expanding possibilities for student participation in online learning environments for practice-based teaching - Yndigegn, Signe Louise; Gammeltoft Gerwien , Rikke (Tidsskriftet Læring og Medier (LOM), 2022)
Developing primarily practice-oriented university courses for an online format challenges pedagogical ideas about learning communities, participation, and involvement in learning situations. Here, we report on a didactic design experiment, the aim of which was to design an online learning environment that supported practice-based learning and in which possibilities for participation were strengthened and expanded. The experiment was conducted during a 14-week university course on co-design, in which the teachers designed different digital tools and learning activities to strengthen the students’ feelings of belonging and community and student-to-student inspiration. The topics discussed in this paper include how to rethink teaching practices in relation to online digital learning spaces and—a new practice that emerged from the design experiment— how to create “in-between spaces.” These spaces can be considered slow spaces that support reflection and discussion, are less exposed, and can be created within and between lectures.